1982
DOI: 10.1177/001872088202400610
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Preferred Shapes for Warning Labels

Abstract: An examination was made of 19 different geometric shapes of warning labels, using the method of paired comparisons. Sixty-six college students viewed slides of all pairs of the shapes and each time selected the shape that was the preferred indicator of warning. An ordinal scaling method was used to evaluate the differences among the shapes. Results show that the triangle on its vertex was the preferred warning indicator among the shapes tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 3 publications
2
27
0
1
Order By: Relevance
“…The distinction for arousal strength among the five shapes was significant, except for UPRIGHT TRI-ANGLE and INVERTED TRIANGLE. The sequence of arousal strength for the five shapes was almost consistent with the results found by Riley et al (1982), except that the rank order of DIAMOND and UPRIGHT TRIANGLE was reversed.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The distinction for arousal strength among the five shapes was significant, except for UPRIGHT TRI-ANGLE and INVERTED TRIANGLE. The sequence of arousal strength for the five shapes was almost consistent with the results found by Riley et al (1982), except that the rank order of DIAMOND and UPRIGHT TRIANGLE was reversed.…”
Section: Discussionsupporting
confidence: 84%
“…UP-RIGHT TRIANGLE and INVERTED TRIANGLE were ranked the first two, and RECT-ANGLE was the shape arousing the weakest strength to people. The sequence of arousal strength from high to low found here was almost consistent with the results of those on western people (Riley et al, 1982), except that the rank of DIAMOND and UPRIGHT TRIANGLE was reversed. Subsequent multiple comparison showed that there was no significant difference of arousal strength between UPRIGHT TRIANGLE and IN-VERTED TRIANGLE ( p Ͼ 0.05).…”
Section: Shapesupporting
confidence: 90%
See 2 more Smart Citations
“…Debido a los pobres resultados obtenidos, resumidos anteriormente, un gran número de investigadores, entre los que citamos a Myers et al (1981), Daube (1982), Purdy y Luepnitz (1982), Riley et al (1982), Bhalla y Lastovicka (1984), Linthwaite (1985), Wogalter et al (1987), Magat et al (1988), Popper y Murray (1989), Wogalter et al (1989), Cragg (1990), Jaynes y Boles (1990), Young y Wogalter (1990), Beede, Lawson y Shepherd (1991), Young (1991), Laughery et al (1993), Barlow y Wogalter (1993), Fischer et al (1993), Naett y Howie (1993), Borland (1997), Liefeld (1999), Mahood (1999), Nilsson (1999), Duffy y Burton (2000), Hammond et al (2003), Hammond (2004), Hoeck et al (2005) y Hammond et al (2006), han cuestionado los esfuerzos necesarios para conseguir que las advertencias sanitarias sean más eficaces. Para ello, han experimentado con distintos elementos, como el tamaño (incremento de las palabras y formato de los anuncios), la forma (formas originales y presencia de iconos), el contraste de colores, la longitud del texto (más corto, más directo y simple), el contenido y el tono (uso de visuales chocantes).…”
Section: Revisión De La Literaturaunclassified